Contemporary Trends and Outcomes of Percutaneous and Surgical Aortic Valve Replacement in Patients With Cancer. Issue 2 (21st January 2020) - Guha, Avirup; Dey, Amit K.; Arora, Sameer; Cavender, Matthew A.; Vavalle, John P.; Sabik, Joseph F.; Jimenez, Ernesto; Jneid, Hani; Addison, Daniel
Abstract : Background: Patients with cancer and severe aortic stenosis are often ineligible for surgical aortic valve replacement (SAVR). Patients with cancer may likely benefit from emerging transcatheter aortic valve replacement (TAVR), given its minimally invasive nature. Methods and Results: The US‐based National Inpatient Sample was queried between 2012 and 2015 using International Classification of Diseases, Ninth Revision, Clinical Modification ( ICD‐9‐CM ), codes to identify all hospitalized adults (aged ≥50 years), who had a primary diagnosis of aortic stenosis. We examined the effect modification of cancer on the relative use rate, outcomes, and dispositions associated with propensity‐matched cohort TAVR versus SAVR. Overall, 47 295 TAVRs (22.6% comorbid cancer) and 113 405 SAVRs (15.2% comorbid cancer) were performed among admissions with aortic stenosis between 2012 and 2015. In the year 2015, patients with cancer saw relatively higher rates of TAVR use compared with SAVR (relative use rateTAVR versus relative use rateSAVR, 67.8% versus 57.2%; P <0.0001). Among patients with cancer, TAVR was associated with lower odds of acute kidney injury (odds ratio, 0.64; 95% CI, 0.54–0.75) and major bleeding (odds ratio, 0.44; 95% CI, 0.38–0.51]), with no differences in in‐hospital mortality and stroke compared with SAVR. In addition, TAVR was associated with higher odds of home discharge (odds ratio, 1.92; 95% CI, 1.68–2.19) compared with SAVR among patients with cancer. Lower risk of acute kidney injury was noted in cancer versus noncancer ( P <0.001) undergoing TAVR versus SAVR in effect modification analysis. Conclusions: TAVR use has increased irrespective of cancer status, with a greater increase in cancer versus noncancer. In patients with cancer, there was an association of TAVR with lower periprocedural complications and better disposition when compared with patients undergoing SAVR.